Administrative empowerment and a course in promoting confidence among school principals - Howari, Afaf Radi (Journal of Educational and Psychological Sciences, 2020)
The study aimed to demonstrate the role of administrative empowerment in enhancing trust among school principals in the Tayyibah and Wasatiyyah Brigades, where the descriptive approach was used. The study used the questionnaire as a tool for the study to reach its goals; statistical program (SPSS) was used to process data statistically and to extract the results The study community included school principles working in the directorate of education in the Tayyibah and Al wasatia, The study sample consisted of (50) principals, the results showed that there is a large role for administrative empowerment in enhancing trust among school principals, With average ranging between (4.1- 3.3 out of 5) for the four areas of empowerment. Based on the results, the researcher presented a set of recommendations and proposals to enhance administrative empowerment and activate its role in enhancing confidence among school principals.
Keywords: administrative empowerment; the role confidence building; the Al- Wasatiya and Taibah brigades